The Structure of Trust in China and the U.S - Chan, Ho-Kong; Lam, Kit-chun; Liu, Pak-wai (2011)
This article investigates the structure of trust in China and compares it with the U.S., using the 2000 and 2005 waves of the World Value Survey (WVS). We analyze two dimensions of trust – trust in people and trust in major companies. It is found that the level of trust has remained stable in China within the 5-year period. On the other hand, trust in major companies has declined dramatically in U.S. while trust in people has increased slightly. The structure of trust in companies is different from trust in people. For both countries, individuals with higher education tend to have a higher level of trust. Individuals who are divorced tend to have lower trust in people. Individuals who think that other people are fair are more likely to trust in people. Preference for competition has a positive effect on trust in major companies. On the other hand, some differences between the two countries are observed. Perception of fairness does not affect trust in major companies in China, while it has a positive effect in U.S. in year 2006. Preference for equality has a negative effect on trust in major companies in U.S. but no significant effect in China. The pattern of trust and its changes over time may reflect differences in market conditions in the two economies.
Keywords: China; Competition; Fairness; Perception; Trust